2007
DOI: 10.1128/mcb.01867-06
|View full text |Cite
|
Sign up to set email alerts
|

The Ternary Complex Factor Net Is Downregulated by Hypoxia and Regulates Hypoxia-Responsive Genes

Abstract: Hypoxia and the Net ternary complex factor (TCF) regulate similar processes (angiogenesis, wound healing, and cellular migration) and genes (PAI-1, c-fos, erg-1, NOS-2, HO-1, and vascular endothelial growth factor genes), suggesting that they are involved in related pathways. We show here that hypoxia regulates Net differently from the other TCFs and that Net plays a role in the hypoxic response in vivo in mice and in cells. Hypoxia induces Net depletion from target promoters, nuclear export, ubiquitylation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 51 publications
(55 reference statements)
2
32
0
Order By: Relevance
“…Thus, Net appears to be an indirect modulator of HIF-1a protein expression. We have previously shown that Net is downregulated in hypoxia, and that Net contributes to the hypoxic induction of several genes, egr-1, c-fos and PAI-1 (Gross et al, 2007). Our current study shows that the role of Net is not limited to a small number of genes.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…Thus, Net appears to be an indirect modulator of HIF-1a protein expression. We have previously shown that Net is downregulated in hypoxia, and that Net contributes to the hypoxic induction of several genes, egr-1, c-fos and PAI-1 (Gross et al, 2007). Our current study shows that the role of Net is not limited to a small number of genes.…”
Section: Discussionmentioning
confidence: 62%
“…We have previously shown that Net mutant mice subjected to chemically induced hypoxia have altered haematocrit levels (Gross et al, 2007). This study identifies various pathways that could be explored to understand this phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations